Penerapan SMAC Framework dan Kinerja UMKM Kuliner: Pengaruh Moderasi Pemanfaatan Analitik Data - Febrianty, Febrianty; Divianto; Sentanu, I Gede Eko Putra Sri (Information Technology and Science (ITScience), 2025)
Latar belakang: This study examines the relationship between the implementation of the SMAC Framework (Social, Mobile, Analytics, and Cloud technologies) and the business performance of culinary MSMEs in Bandar Lampung, with a focus on how data analytics utilization moderates this relationship to support sustainable development goals (SDGs). Metode penelitian: Using a mixed-methods design, the study combines quantitative analysis with SEM-PLS and qualitative insights from open-ended survey responses collected from culinary MSMEs in Bandar Lampung, supported by a systematic literature review on digital transformation and the SMAC Framework. Hasil penelitian: : Analysis of data from 100 culinary MSMEs shows that the SMAC Framework significantly enhances business performance, and the moderating effect of data analytics utilization further strengthens this relationship (? = 0.25, p = 0.021); qualitative feedback confirms that data-driven decision-making improves operational efficiency and innovation, aligning with SDG No. 8, 9, and 10. Kesimpulan: Based on the results of the analysis, this research concludes that the implementation of the SMAC Framework has a significant positive influence on the performance of culinary MSMEs in Bandar Lampung. The integrated use of digital technology—including Social, Mobile, Analytics, and Cloud aspects—has been proven to increase operational efficiency, product innovation, and expand market reach. In addition, the use of analytical data as a moderator variable strengthens the relationship between the implementation of the SMAC Framework and MSME performance.